ANALISIS PERBANDINGAN KOMPOSISI NASABAH DAN DPK (DANA PIHAK KETIGA) PADA BANK PEMERINTAH DAN BANK SWASTA DI KALIMANTAN BARAT - B01108028, RIO MEGAWIGUNA (Jurnal Pembangunan dan Pemerataan, 2014)
This study entitled "Comparative Analysis of Customer Composition And TPF (Third PartyÂ Funds) In Government Banks and Private Banks In West Kalimantan". This study aims todetermine and analyze the comparative composition of customers and deposits (Deposit s) atState Bank and Private Bank in West Kalimantan. In this study using a qualitative approach,the research object composition ratio of customers and deposits (Deposits) at State Bank andPrivate Bank obtained from the central bank (Bank Indonesia) and Pontianak branch of BPS(Central Bureau of Statistics) of the province of West Kalimantan.Â Based on the results of data analysis, the composition of the aspects of customer depositgrowth and the number of customers in the state bank is greater than the private banks inWest Kalimantan. In addition, the performance of banks as seen from LDR BankGovernment and private banks have a comparison, where the LDR at State Bank is greaterthan the private banks.Keywords: Composition Customers, Deposits, Government Bank, Private